2018
DOI: 10.1038/s41375-018-0144-7
|View full text |Cite
|
Sign up to set email alerts
|

New therapeutic opportunities from dissecting the pre-B leukemia bone marrow microenvironment

Abstract: The microenvironments of leukemia and cancer are critical for multiple stages of malignancies, and they are an attractive therapeutic target. While skeletal abnormalities are commonly seen in children with acute lymphoblastic leukemia (ALL) prior to initiating osteotoxic therapy, little is known about the alterations to the bone marrow microenvironment during leukemogenesis. Therefore, in this study, we focused on the development of precursor-B cell ALL (pre-B ALL) in an immunocompetent BCR-ABL1+ model. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 65 publications
3
38
0
Order By: Relevance
“…5B). The replacement of normal hematopoiesis has been suggested to occur during leukemic progression through different mechanisms, including niche occupancy by hyperproliferative cells and induction of a leukemic microenvironment unsuitable for normal hematopoiesis (Balandrán et al, 2017;Cheung et al, 2018). In a previous work, we reported the NFkB-induced expression of CXCR7 concomitant to the perturbation of the CXCR4/CXCL12 and VCAM-1/VLA-4 integrin axes (Enciso et al, 2016), consistent with experimental evidence of its involvement in immune cell recruitment and tumor metastasis (Alampour-Rajabi et al, 2015;Tarnowski et al, 2010;Torossian et al, 2014;Chang et al, 2018).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…5B). The replacement of normal hematopoiesis has been suggested to occur during leukemic progression through different mechanisms, including niche occupancy by hyperproliferative cells and induction of a leukemic microenvironment unsuitable for normal hematopoiesis (Balandrán et al, 2017;Cheung et al, 2018). In a previous work, we reported the NFkB-induced expression of CXCR7 concomitant to the perturbation of the CXCR4/CXCL12 and VCAM-1/VLA-4 integrin axes (Enciso et al, 2016), consistent with experimental evidence of its involvement in immune cell recruitment and tumor metastasis (Alampour-Rajabi et al, 2015;Tarnowski et al, 2010;Torossian et al, 2014;Chang et al, 2018).…”
Section: Discussionsupporting
confidence: 82%
“…Upon simulation of the continuous model with NFkB constitutive, null and intermediate activation, we infer that NFkB is dispensable for B cell differentiation. However, its high activation induces an aberrant attractor and a longer transitory stage with myeloid potential, redirecting differentiation toward a non-lymphoid lineage, as previously reported in ALL murine models (Cheung et al, 2018). Moreover, a conspicuous population with a pre-B like phenotype and particular niche requirements developed upon the intermediate activation of NFkB, emerging as a perturbation in the epigenetic landscape (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…These results are consistent with those of other studies including that of Colmone et al in which Nalm6 cells colonized CXCL12 niches in the BM of xenografted mice, which subsequently resulted in marked downregulation[43,202]. A recent report showed that leukemic cells can promote osteoclast-mediated bone resorption through the production of receptor activator of nuclear factor κB ligand (RANKL)[203]. This is in accordance with a previous report that demonstrated in a T-ALL mouse model that ALL cell engraftment in theBM of mice was associated with bone microenvironment remodeling due to a marked loss of osteoblastic cells [204].…”
supporting
confidence: 92%
“…In ALL, modifying the leukemic microenvironment to reverse the phenotype of dormant blast cells could be also a viable option [45]. This could be achieved by restoring a healthy microenvironment, for example by using bisphosphonates that could prevent bone degradation, which is observed in leukemia pathogenesis [203,204]. Another possible strategy could target signaling pathways that are upregulated upon the interaction of malignant cells with their microenvironment, such as the TGFβ and HIF1α pathways, for which several preclinical or early clinical studies have been published [246,247].…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Previous studies have shown that the use of ZA may significantly enhance apoptosis by elevating ROS levels in prostate carcinoma and salivary adenoid cystic carcinoma cell models [ 80 , 81 ]. In addition, it is reported that ZA induces cancer cells apoptosis by inhibiting the production of RANKL in leukemia [ 82 ]. Moreover, ZA also increases the expression of pro-apoptotic protein Bax and decreases the expression of anti-apoptotic protein Bcl-2, increases the permeability of cell membrane, and induces caspase-3 dependent pathway, and finally induce apoptosis [ 43 ].…”
Section: Anticancer Effects Of Zamentioning
confidence: 99%